Albert Maysles - McElhaney, Joe, 1957- (Contemporary film directors., 2009)
Albert Maysles has created some of the most influential documentaries of the postwar period. Such films as Salesman, Gimme Shelter, and Grey Gardens continue to generate intense debate about the ethics and aesthetics of the documentary form. In this in-depth study, Joe McElhaney offers a novel understanding of the historical relevance of Maysles. By closely focusing on Maysles's expressive use of his camera, particularly in relation to the filming of the human figure, this book situates Maysles's films within not only documentary film history but film history in general, arguing for their broad-ranging importance to both narrative film and documentary cinema. Complete with an engaging interview with Maysles and a detailed comparison of the variant releases of his documentary on the Beatles (What's Happening: The Beatles in the U.S.A. and The Beatles: The First U.S. Visit), this work is a pivotal study of a significant filmmaker.